Nanotechnology for cosmetics applications—a journey in innovation - Longo, João Paulo Figueiró; Camargo, Nichollas Serafim; Ferreira, Guilherme Alves; Cardador, Camila Magalhães; Corrêa, Marcos Antônio [UNESP] (Elsevier, 2022)
The cosmetic sector was one of the first industries that adopted nanotechnology in their products. During the 1980s, some European brands incorporated liposome nanocarriers in cosmetic products. Today, thousands of companies develop and use different nanotechnologies in the cosmetic sector. Moreover, due to this historical development, a number of applications for nanoparticles have been proposed at different stages of product development. In this chapter, we will present nanocosmetic activities as an innovative strategy to improve different areas of cosmetology, from the development of new ingredients to their applications in skin or hair-care products. The main benefits include active dispersion, protection of chemical instabilities, controlled release of active ingredients, and improved product effectiveness. The objective here is to present how nanotechnology affects cosmetic development in the technological journey from the conception of the product, moving through industrial production, and finally providing benefits for end users.
Keywords: cosmetics; end users; Nanotechnology; scaled-up production; technology translation